Wow good job lol- umm get into it I guess
Answer:
f(-3) = -3
Step-by-step explanation:
Step 1: f(x) means "f of x" and f(-3) means "f of -3", so you have to replace all the "x" letters in the function with the value -3.
![f(x)=x^4+3x^3-x^2+6\\f(-3)=(-3)^4+3(-3)^3-(-3)^2+6](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E4%2B3x%5E3-x%5E2%2B6%5C%5Cf%28-3%29%3D%28-3%29%5E4%2B3%28-3%29%5E3-%28-3%29%5E2%2B6)
Step 2: Apply the exponents. <em>Make sure you remember to put in the -3 and not just 3.</em>
![f(-3)=81+3(-27)-9+6](https://tex.z-dn.net/?f=f%28-3%29%3D81%2B3%28-27%29-9%2B6)
Step 3: Use BEDMAS rules to complete the calculation.
![f(-3)=81-81-9+6](https://tex.z-dn.net/?f=f%28-3%29%3D81-81-9%2B6)
![f(-3)=-3](https://tex.z-dn.net/?f=f%28-3%29%3D-3)
Therefore the answer is f(-3) = -3.
57 degrees because vertical angles are the same measure
Let's solve this by creating an equation.
Let X = the second factor
![X\times90=7000\\X = 7000\div90\\X= 77.77777](https://tex.z-dn.net/?f=X%5Ctimes90%3D7000%5C%5CX%20%3D%207000%5Cdiv90%5C%5CX%3D%2077.77777)